Long-term Outcome of Vascularized Fibular Bone Graft Reconstruction for Upper Limb Osteosarcoma: A Case Report - Revanth Thiruvarul Selvan; Gutta Charith; Viveksheel Bhatti; Gopinath Menon (Journal of Orthopedics and Joint Surgery)
Introduction: Osteosarcoma is a primary malignant bone tumor. In older days, the mainstay treatment was used to be amputation of the affected extremity. But nowadays, limb salvage procedures with biological reconstruction are done due to their better long-term outcomes. Materials and methods: This is a case report of a 34-year-old female who underwent left proximal humerus osteosarcoma wide excision and reconstruction with free vascularized fibula graft and chemotherapy 12 years back. During these 12 years, the patient had gradual improvement in her movements in her left upper limb and overall outcome. Her Musculoskeletal Tumor Society (MSTS) score has also improved. Conclusion: Malignant tumors of a long bone can be treated with a limb salvage procedure by biological reconstruction using a vascularized bone graft instead of amputation or endoprosthesis reconstruction for a better long-term outcome.